Implementasi Metode Small Group Discussion untuk Meningkatkan Aktivitas Belajar Fikih Peserta Didik - Naufal, Naufal; Soimah, Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
The aims of this study is: 1) Knowing the use of the Small Group Discussion method in fiqhlearning for class X MA tanbihul Ghofilin Bawang students; 2) Knowing the difference betweenlearning activities using the Small Group discussion method and those who do not use the smallgroup discussion method in class X MA Tanbihul Ghofilin students; 3) Knowing the increasein learning activities using the small group discussion method for class X MA TanbihulGhofilin Bawang students. The research according to experimental methods using nonequivalent control group design. The subjects in this study were students of class X Agama 3and X Agama 4 MA Tanbihul Ghofilin which totaled 60 students who were divided into twogroups, namely class X Agama 3 as the Experimental class and Class X Religious 4 as thecontrol class. Learning begins with providing pretest questions to find out the extent of studentlearning activities. Experimental students were given learning using the small group discussionmethod while the control group used conventional learning methods. The experimental groupand the control group were given the final test in the form of posttest questions in writing. Thenthe results were processed, analyzed, and compared using a t-test and a scor gain test todetermine the differences and activities between the two groups to be studied. The resultsshowed that there were differences in learning activities between the experimental class andthe control class with evidenced by the t-test and the control class with evidenced by the t-testcalculation showing tcount of count 2,0001 > ttable 10.6 with a significance level 0f 5 % anddegress of freedom 58. It was proveb by the calculation of N-gain of 0,76 with category